Photo fermentative biohydrogen production potential using microalgae–activated sludge co-digestion in a sequential flow batch reactor (SFBR). Issue 46 (18th October 2022) - Javed, Muhammad Asad; Aly Hassan, Ashraf
Abstract : Biohydrogen (bioH2 ) is a sustainable energy source that can produce carbon-free energy upon combustion. Abstract : Biohydrogen (bioH2 ) is a sustainable energy source that can produce carbon-free energy upon combustion. BioH2 can be generated from microalgae by photolytic and anaerobic digestion (AD) pathways. The AD pathway faces many challenges when scaling up using different bioreactors, particularly the continuous stirred tank reactor (CSTR) and sequential flow batch reactor (SFBR). Therefore, the performance characteristics of SFBR were analysed in this study using Chlorella vulgaris and domestic wastewater activated sludge (WWAS) co-culture. An organic loading rate (OLR) of 4.7 g COD L −1 day −1 was fed to the SFBR with a hydraulic retention time (HRT) of five days in the presence of light under anaerobic conditions. The pH of the medium was maintained at 6 using a pH controller for the incubation period of 15 days. The maximum bioH2 concentrations of 421.1 μmol L −1 and 56.6 μmol L −1 were observed in the exponential and steady-state phases, respectively. The effluent had an unusually high amount of acetate of 16.6 g L −1, which remained high with an average of 11.9 g L −1 during the steady state phase. The amount of bioH2 produced was found to be inadequate but consistent when operating the SFBR with a constant OLR. Because of the limitations in CSTR handling, operating a SFBR by optimizing OLR and HRT might be more feasible in operation for bioH2 yield in upscaling. A logistic function model was also found to be the best fit for the experimental data for the prediction of bioH2 generation using co-culture in the SFBR.